Departamentalización e innovación en las micro, pequeñas y medianas empresas de Colombia (2016)
The organizational structure is a subject of high academic interest because of its relationship with the strategy and other business aspects, so the aim of this work is to determine the impact of the departmentalization on innovation of micro, small, and medium enterprises in Colombia, specifically on products/services, processes, management and globally. To do that, an empirical, transversal and inferential study with linear regressions was conducted with 1201 managers of these organizations, who were asked about the number of departments and innovation in their firms. The results show the organizations studied in a medium level of departmentalization and confirm the positive impact of specialization in the structure on the different types of innovation analyzed (except for processes). It is concluded that the Academia and development agencies should support companies in their process of departmentalization, balancing costs and benefits.